PARIWISATA ISLAMI DI DANAU LAUT TAWAR KECAMATAN BINTANG KABUPATEN ACEH TENGAH - Ayu Kinnara (Perspektif Sosiologi, 2013)
The Laut Tawar Lake is one of  lake in Takengon, regency of central Aceh. The potency of the natural panorama of the lake is same as other tourism object in Nanggroe Aceh Darussalam (NAD). The beautiful panorama and the fresh air in addition to the history of the lake and any new  finding as the tourism object that satisfy its visitors. As well as the enforcement of  Isamic Shari’a, this tourism object to be Islamic based tourism object. The problem in this research is what a respond of the local people to the development of tourism object of  Laut TAwar Lake by the implementation of  Islamic Shari’a. Based on the result of research it concluded that since the enforcement of  Islamic Shari’a, it also applied the Islamic based tourism, while it has not yet implemented actually because there is not socialization either by the officers of  Islamic Shari’a Office  oicer Tourism Office . Therefore, the local people did not know this Islamic tourism. Keywords : Tourism, Tourism Development, Islamic Shari’a, Tour.